NATURAL GEOGRAPHICAL CONDITIONS OF THE FERGANA VALLEY – THE MAIN FACTOR IN THE DEVELOPMENT OF HORTICULTURE - Turdibekova, Zamira Muzapbarovna; Makhmudova, Manzuraxon Juraevna (SCIENCE and SOCIETY, 2026)
The natural geographical conditions and agro-climatic factors of the Fergana Valley are naturally the most favorable for the development of horticulture. This feature has led to the formation of an intensive horticultural, vegetable and melon growing region. Today, the valley has not only specialized horticultural farms, but also fruit processing industrial enterprises, associations and workshops, which have a positive impact on the export of products. As a result, the Fergana Valley has formed agro-industrial companies of national significance.